A REVIEW OF RADIOMETRIC DATING TECHNIQUES FOR CLAY MINERAL CEMENTS IN SANDSTONES - Hamilton P.J. (My University, 2002)
The principles underlying the application of radiometric dating methods to determining the timing of clay-mineral cementation in sandstones are reviewed. Most previous work has centred on the use of the Rb–Sr and K–Ar schemes for age determinations on separated glauconites, illites and mixed-layer illite–smectites. Some of the difficulties encountered in attempting to date clay-mineral diagenesis include other mineral contaminants, potentially contaminant elements in cation exchange sites, separation of multiple growths of a particular mineral formed at different times in the same sandstone, isolation of the mineral phase of interest in a pure state and the need for three or more cogenetic phases required for the application of some radiometric schemes. As experience has been gained, the need to carefully characterize the phase being analysed, increased measurement sensitivity and increasingly sophisticated methods of sample preparation have resulted in clay mineral dates that can be related to a diagenetic age with more confidence. Additionally, much has been learnt of the processes of clay-mineral diagenesis.More recently there has been a shift in emphasis in clay-mineral geochronology to greater use of the 40Ar/39Ar method for dating clay-mineral diagenesis in fine-grained sediments. The associated advantage of being more suitable for extremely small samples, on the order of tens of micrograms that can be readily screened for contaminants, is an attractive feature for potential application to sandstones. Although considerable research remains to be done, there is considerable scope with this technique for application to sandstones when coupled with laser microprobe heating of clay cements in situ in thin-sections.